Giving the past a future : essays in archaeology and rock art studies in honour of Dr. Phil. h.c. Gerhard Milstreu - Milstreu, Gerhard,; Dodd, James,; Meijer, Ellen, (Archaeopress Publishing Ltd, 2018)
This volume celebrates the work of Dr. Phil. h.c. Gerhard Milstreu in his 40th year as director of Tanum Museum of Rock Carving and Rock Art Research Centre, Sweden. A feast of scholarly contributions pay respect to and acknowledge Gerhard's achievements in the fields of rock art documentation, research, international collaboration and outreach.